PREPARING STUDENTS FOR TEACHING SCIENCE SUBJECTS BASED ON ADEQUATE MODELS (British Journal of Global Ecology and Sustainable Development, 2026)
This article serves as a methodological guideline aimed at further improving the methodological training of students in natural sciences based on adequate models. The organization of the educational process in natural sciences involves collaboration between schools and preschool education institutions. This cooperation significantly contributes to the formation of students as competent professionals in their respective fields. The role of adequate models is indispensable for the thorough study of living organisms encountered in nature within the educational process. Therefore, lessons become clear, engaging, and yield effective results for students. Adequate models, which specifically facilitate the organization of natural phenomena in the classroom, presenting exact models of the organisms to be studied, and recreating a natural environment during the lesson, serve as an attention-grabbing and stimulating teaching tool.